Intensive Care Medicine Annual Update 2008 - Vincent, Jean-Louis.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
The Update compiles the most recent developments in experimental and clinical research and practice in one comprehensive reference book. The chapters are written by well recognized experts in the field of intensive care and emergency medicine. It is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.
Genetic Factors -- Cardiac Issues -- Cardiopulmonary Resuscitation -- Emergencies -- Poisonings -- Acute Respiratory Failure -- Ventilatory Support -- Tracheostomy -- Infections -- Cellular Mechanisms in Sepsis -- Sepsis Therapies -- Metabolic Alterations -- Fluid Management.-Acute Kidney Injury -- Hemodymic Assessment and Management -- Tissue Oxygenation -- Anticoagulants in Organ Failure -- Acute Bleeding -- Hepatic Disease -- Neurological Crises -- Analgesia and Sedation -- Outcomes.
Keywords: Medicine; Emergency medicine; Critical care medicine; Internal medicine; Medicine & Public Health; Intensive / Critical Care Medicine; Emergency Medicine; Internal Medicine; Electronic books